If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-3) + -2(x + 6) = -5 -3 + -2(x + 6) = -5 Reorder the terms: -3 + -2(6 + x) = -5 -3 + (6 * -2 + x * -2) = -5 -3 + (-12 + -2x) = -5 Combine like terms: -3 + -12 = -15 -15 + -2x = -5 Solving -15 + -2x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -2x = -5 + 15 Combine like terms: -15 + 15 = 0 0 + -2x = -5 + 15 -2x = -5 + 15 Combine like terms: -5 + 15 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| -1=-.5x+2 | | 9w+33=3(w-9) | | 825+3.25x=8.20x | | X-(-2)=-6 | | -7y+5=4 | | 900=5e^9x | | (14x-5)+13x=180 | | -15=15q-50-5p | | (8x-1)(5x+1)=0 | | (5k+3)(k-2)=0 | | -6(3+2k)=-78 | | 5(5r+5)=-100 | | (2x+8)(x-3)=154 | | H=16t(7-t)+10 | | 3t^6*3t^2= | | 6c=11 | | -46=-6x+2 | | Sin^2(x)-sin(x)-1=0 | | 6(x-4)+10=2x-12 | | 115x+25+10x=1400 | | 11=-3-x | | 4v=7 | | 2(m-3)-(2m+6)= | | 9c+8=3 | | x+(x+7)=60 | | N^2-9n+19=0 | | -11=4-8x+1 | | 5n-7=4 | | 48=x^4-5x^2+4 | | 8b+11+2b=2b+2 | | 2(x+2)=16+4x | | 2y=(k+4)x-1 |